2011
DOI: 10.1161/circulationaha.110.958769
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Blood Pressure in Preschool Children

Abstract: Background-Hypertension is the leading risk factor for cardiovascular disease. Although accumulating evidence suggests tracking of blood pressure from childhood into adult life, there is little information regarding the relative contributions of genetic, prenatal, biological, behavioral, environmental, and social determinants to childhood blood pressure. Methods and Results-Blood pressure and an array of potential anthropometric, prenatal, environmental, and familial risk factors for high blood pressure, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 36 publications
14
102
2
13
Order By: Relevance
“…Nevertheless, our prevalence of prehypertension/hypertension was lower than the 14% observed in a large Australian cohort (~2000 preschoolers) (Gopinath et al, 2011a). In agreement with recent literature in preschoolers, we observed a trend for higher SBP %ile in girls compared to boys (Simonetti et al, 2011).…”
Section: Blood Pressuresupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, our prevalence of prehypertension/hypertension was lower than the 14% observed in a large Australian cohort (~2000 preschoolers) (Gopinath et al, 2011a). In agreement with recent literature in preschoolers, we observed a trend for higher SBP %ile in girls compared to boys (Simonetti et al, 2011).…”
Section: Blood Pressuresupporting
confidence: 93%
“…While older studies have observed an inverse relationship between BP and aerobic fitness in preschoolers (Gutin et al, 1990;Shea et al, 1994), it is not known how PA relates to BP in this young age group. PA may indirectly affect BP through energy balance and body composition, as preschoolers with higher BMIs have elevated SBP and DBP (Simonetti et al, 2011;Gopinath et al, 2011a). For the first time, this thesis will characterize the relationship between BP and PA in preschoolers.…”
Section: Relationships Between Physical Activity and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons with other studies are difficult due to lack of data in preschool-aged children. Although childhood BP is influenced by genetic and prenatal factors, as well as by dietary habits and environmental factors, such as passive smoking, 28 our results have importance from a primary prevention perspective. First, children who are overweight or obese at an early age have greater odds of having CVD risk factors such as BP [29][30][31][32] as well as an increased risk for developing cardiovascular and metabolic conditions later in life.…”
Section: Discussionmentioning
confidence: 74%
“…The heart and vascular system are highly vulnerable to tobacco smoking. Discouraging maternal smoking and maintaining a strictly smoke-free environment are of great importance due to the accumulating evidence on the importance of fetal and early life factors in determining CV risk (209). In adolescents, promotion of smokefree rules at home may help prevent the uptake of cigarettes.…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 99%